P280 Reducing the overprescribing of oral corticosteroids in IBD using a steroid assessment tool. (16th January 2018) - Scott, G; Roads, N; Lewis, W
Abstract: Background: Treatment for IBD has two main goals – eliminate symptoms of active disease and maintain remission. Clinical studies demonstrate that steroids help induce remission in both active Crohn's disease (CD) and active ulcerative colitis (UC). However, further research demonstrates steroids are not able to maintain remission and long-term use can increase susceptibility to infections, cataracts, osteoporosis and myopathy. As a consequence achieving steroid-free remission is considered a clinical objective for most IBD treatment strategies and an important goal for patient QoL (Quality of Life). Methods: In an effort to optimise the use of steroids in the treatment of IBD, collaboration between 14 IBD consultants and nurses and AbbVie in 2014 resulted in the development of a secure web-based steroid assessment tool (SAT), enabling clinicians to monitor steroid use within their clinic setting. In Kent, UK, 3 IBD nurses were keen to work with AbbVie on a collaboration using SAT. The aim of the Kent Steroid project was to understand the use of steroids for IBD treatment and initiate small changes that lead to improved IBD patient quality of care. The assessment was on going with over 700 IBD patients entered into the SAT. Results: Consistent with previously reported data from the Nationwide UK steroid study, excess steroid use was more likely in UC vs. CD. However, in contrast to the nationwide audit, the Kent Steroid Audit reported that 21% of steroid use was in excess of European guidance compared with 13.8% nationally. A further audit this year has demonstrated that the steroid excessive use has dropped from 21% to below the national average. Furthermore, the prescription of bone protection agents and the dose/duration of steroids were inconsistent between hospitals in the previous audit. It showed 56% compliance with prescribing bone protection, whereas this audit has now demonstrated a 88% compliance factor. Conclusions: The Kent Steroid project concluded that steroid use in excess of ECCO guidance was more than the national level. As a result, small changes by the Kent IBD nurses have led to: improved patient steroid education; highlighting steroid use on hospital letters; speaking with general practitioners when standard steroid practice has not been followed. A re-assessment with SAT was undertaken in 2017 to compare levels of steroid use. It also demonstrated an improvement in bone protection prescribing. These small changes already implemented have definitely improved the delivery of high quality and safe care of IBD patients in Kent.